Analysis of the Application of Income Tax on In-kind Rewards and the Enjoyment of Relationships with Work Seen from the Aspect of Justice - Margaretha Angela Kurniawan; Andang Wirawan Setiabudi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research aims to examine how the concept of fairness in good taxation, as well as whether the implementation of the Minister of Finance Regulation Number 66 in the year 2023 is following the aspect of fairness. This research was conducted using primary data. This primary data was collected by the researcher directly from the first source or the location where the research object was carried out. The primary data in this study includes observation results, as well as interviews with workers directly involved in the tax deduction on nature. This research was conducted from October 2024 to November 2024. Fairness is not arbitrary, biased, or one-sided. Tax is a mandatory payment to the state, which is obligatory according to the Law, without direct reciprocal benefits, and is used for the benefit of the state for the greatest prosperity of the people. Natura and/or benefits are rewards received not in the form of money. From the results of the research, it can be concluded that taxes currently adhere to the principle of vertical equity and that the average individual or worker has the ability to pay taxes, in general, the implementation of PMK 66/2023 is in accordance with the principles of justice in a good taxation system. However, there are several recommendations for this research, namely, the government must create a tax system that is easy for the public to understand. An easily understandable tax system will encourage the public to learn and understand how the tax system works in Indonesia.